Factors affecting the entrepreneurial behavior of students in Hanoi City: The role of entrepreneurial intention and innovation capacity - Lan, Do Thi Ngoc; Ha, Thai Van; Hau, Nguyen Van; Thanh, Doan Tat (Edelweiss Applied Science and Technology, 2025)
Recognizing the importance of startups, the Vietnamese government implements many preferential and supportive policies to encourage the development of startups and individuals, especially students, following the "Supporting Students to Start a Business until 2025" proposal. The purpose of this study is to explore the impact of innovation capacity on the entrepreneurial behavior of university students in Hanoi City. It also examines entrepreneurial intention as an intermediate variable in the relationship between innovation capacity and entrepreneurial behavior. We used quantitative research methods. The research data was collected using Google Forms with 1,050 valid questionnaires from a survey of university students studying in Hanoi City. The author performed data analysis using linear structural equation modeling (SEM). Research results show a positive relationship between innovation capacity and entrepreneurial behavior through the variable of entrepreneurial intention. Thereby, the authors propose management implications to improve the entrepreneurial behavior of Vietnamese students in today’s emerging economy. This study contributes to the completion of the theoretical framework on the innovation capacity and entrepreneurial behavior of students. Besides, it is also a useful reference for firms and researchers.